Analysis of Space Utilization in the Border Area of Anyer Beach, Serang Regency - Achmad Zukhrova; Arenawati Arenawati; Rina Yulianti (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The attraction of natural beauty, especially coastal areas, has made investors or business people set up various commercial businesses such as villas, hotels, and restaurants. Inappropriate use and arrangement of space is a problem that will continue to arise in the management of coastal areas. The general aim of this research is to find out the impact of space utilization in border areas on Anyer Beach, Anyer sub-district. This research was carried out using a descriptive qualitative approach. Research data was obtained through interviews, documentation, and observation. Then the collected research data will be analyzed through data reduction and presentation. The results of this research show that the management of space utilization in the Anyer tourist area is not yet optimal, especially in controlling environmental and social impacts. Utilization of a coastal border area that does not comply with existing regulations and supervision does not appear to be optimal with the existence of hotels or commercial buildings. The lack of empowerment of community members and community involvement around tourist attractions seems to be lacking in the process of managing tourism areas or areas. Therefore, proper use of coastal border areas is a way of resolving conflicts over excessive resource exploitation in the Anyer Beach tourist area.